2016
DOI: 10.1016/j.jsxm.2016.06.009
|View full text |Cite
|
Sign up to set email alerts
|

Patient-Reported Esthetic and Functional Outcomes of Primary Total Laparoscopic Intestinal Vaginoplasty in Transgender Women with Penoscrotal Hypoplasia

Abstract: Introduction Puberty-suppressing hormonal treatment may result in penoscrotal hypoplasia in transgender women, making standard penile inversion vaginoplasty not feasible. For these patients, intestinal vaginoplasty is a surgical alternative, but knowledge on patient-reported postoperative outcomes and quality of life is lacking. Aims To assess patient-reported functional and esthetic outcomes, quality of life, satisfaction, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
93
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 87 publications
(105 citation statements)
references
References 25 publications
1
93
0
2
Order By: Relevance
“…Most studies point out the substantial risks of these surgeries (Horbach et al, 2015), whereas data collection via surveys obtained similarly high self-reported complication rates (Lawrence, 2006). The high number of satisfied respondents found in the present study is comparable to earlier studies (Bouman et al, 2016;Buncamper et al, 2015;De Cuypere et al, 2005;Horbach et al, 2015;Lawrence, 2003;Lawrence, 2006;Nelson, Whallett, & McGregor, 2009;Rehman et al, 1999;Smith et al, 2005;Weigert et al, 2013) and emphasizes the effectiveness of gender-affirming procedures. Yet, most treatment evaluation studies have collected data in a clinical setting, whereas the present study reports on a cohort that was surveyed in their home environment with limited dependence on clinicians (although the participants were invited through the clinics).…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…Most studies point out the substantial risks of these surgeries (Horbach et al, 2015), whereas data collection via surveys obtained similarly high self-reported complication rates (Lawrence, 2006). The high number of satisfied respondents found in the present study is comparable to earlier studies (Bouman et al, 2016;Buncamper et al, 2015;De Cuypere et al, 2005;Horbach et al, 2015;Lawrence, 2003;Lawrence, 2006;Nelson, Whallett, & McGregor, 2009;Rehman et al, 1999;Smith et al, 2005;Weigert et al, 2013) and emphasizes the effectiveness of gender-affirming procedures. Yet, most treatment evaluation studies have collected data in a clinical setting, whereas the present study reports on a cohort that was surveyed in their home environment with limited dependence on clinicians (although the participants were invited through the clinics).…”
Section: Discussionsupporting
confidence: 85%
“…In general, the literature gives high percentages of satisfaction with GAS procedures: breast augmentation 87% to 100% (De Cuypere et al, 2005;Smith, van Goozen, Kuiper, & Cohen-Kettenis, 2005;Weigert, Frison, Sessiecq, Al Mutairi, & Casoli, 2013), vaginoplasty 83% to 100% (De Cuypere et al, 2005;Horbach et al, 2015;Lawrence, 2003;Rehman, Lazer, Benet, Schaefer, & Melman, 1999;Smith et al, 2005), subcutaneous mastectomy 92% to 100% (De Cuypere et al, 2005;Nelson, Whallett, & McGregor, 2009;Smith et al, 2005), and phalloplasty 100% (De Cuypere et al, 2005). Clinical evaluation studies show positive appraisal of both genital functionality and aesthetics after surgery, whereas sexual outcomes were found to be less positive (Bouman et al, 2016;Buncamper et al, 2015). In a cohort of 232 operated trans women, Lawrence (2003) examined the effect of three categories of characteristics on (dis)satisfaction with genital GAS, namely personal characteristics (e.g., age), therapy characteristics (e.g., psychotherapy provided), and psychosocial characteristics.…”
Section: Introductionmentioning
confidence: 99%
“…Recent insurance database analysis and patient-reported outcome studies identified patients as young as 14 years old undergoing a gender-affirming mastectomy 18 19. Some research works suggest there are psychosocial benefits to individuals receiving gender mastectomy in their teens 18 20–22. For both surgical and hormonal gender-affirming care, there are psychosocial and physical benefits for transgender minors.…”
Section: Medical Gender Affirmation: Risks and Benefits In Minorsmentioning
confidence: 99%
“…Age, relationship status (0 = no partner, 1 = partner), and gender identity (0 = binary [male or female], 1 = nonbinary [both male and female or neither male nor female]) were included as control variables. Previous studies have shown the importance of relationship status for sexual satisfaction, sexual activity, and sexual functioning (Bouman et al, 2016;Weyers et al, 2009).…”
Section: Multivariate Analysesmentioning
confidence: 98%